Free Convective Heat And Mass Transfer Radiative Flow Past An Impulsively Started Vertical Moving Plate With Uniform Heat And Mass Flux - .kodidala, Janardhan; Pillai.k, Jagadeeswara; Reddy. G, Viswanatha (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this paper, we studied analytically the thermal radiation effect on free convective flow of a viscous incompressible fluid past an impulsively started vertical plate with flux. The fluid is assumed to be gray absorbing-emitting but not a scattering medium and Rosseland approximation is used to describe the Radiative heat flux. The method of Laplace transform is used to solve dimensionless governing partial differential equations. The resulting velocity, temperature and concentration profiles as well as the skin friction, rate of heat and mass transfer have been obtained. Some important applications of physical interest for different type motion of the plate are discussed numerically through graphs.